WOMEN’S LANGUAGE FEATURES OF DEBBIE IN OCEANS 8 MOVIE (2018) - Mirawati Mirawati; M. Bahri Arifin; Indah Sari Lubis (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
Women and men are different in terms of using language. Women’s language proved that women tend to use language differently than men, by the features use this research focused on women’s language features and the function of those features. It aims to identify women’s language features based on Lakoff’s theory and also to identify the functions of language features that is used by main character in Ocean’s 8 Movie based on Jacobson’s theory. This qualitative research was conducted by applying observation checklist to help the researcher to find out women’s language features. Data were taken from Ocean’s 8 movie script in the form of women’s utterances. The result show that six features uttered by Debbie in Ocean’s 8 Movie (2018). They are lexical hedges or filler , tag question, super polite form, empty adjective, intensifier, and avoidance of strong swears words. Lexical hedges or fillers are the most frequent women’s language features used by Debbie in Ocean’s 8 Movie(2018). Then, the language functions which are served by women’s language of Debbie in Ocean’s 8 Movie (2018) are expressive function and directive function.